Facing Sexual Harassment and Abuse in the Feminizing Museum - trivedi, nikhil; Wittman, Aletheia (Journal of Museum Education, 2018)
Despite the growing number of women in museums, the undervaluing of educational work traditionally associated with women, and labor largely done by women today, persists. This begs the question: in what other ways are women and femmes working in museums undermined despite their growing presence as workers and the emerging centrality of the educational role of museums? In society more broadly, we see how undervaluing women and their labor leads to a spectrum of treatment that can be considered violent. In this spectrum, we include pay and benefit disparities, disempowerment, and marginalization through sexist, homophobic, and transphobic comments and objectification, harassment, threats, verbal, physical, emotional, and financial abuse, and at the far end of the spectrum sexual assault and murder. In this article, we discuss data collected through a survey conducted about incidences of sexual abuse and harassment experienced by museum workers. We explore the results of the survey in relation to the gender-based division of labor and skills among the museum workforce. We look to the responses to this survey as a gauge of how much power women and gender non-conforming people have in their daily work lives in museums and propose actions that could increase empowerment and support.
Keywords: Bibliographie; Myriam; Nettoyer; Sexual violence; feminization; gender equity; labor; museum education; museum workers